(untitled) (Shahroud Journal of Medical Sciences, 2021)
Background: Osteoporosis is a skeletal disease associated with a gradual decline of bone density, as well as a characteristic reduction of bone rigidity and an increased risk of fractures. This study aimed to investigate the effects of four months of core stability training on the bone mineral density (BMD) of the femur neck and lower extremity muscles strength in postmenopausal women. Methods: This study was an interventional semi-experimental one designed with a pre-test/post-test approach. Overall, 30 postmenopausal women aged 48 to 58 years were purposefully selected and then randomly divided into two groups of core stability exercise (weight= 70.73 ± 12.57 Kg) and control (weight= 77.86 ± 7.19 Kg) groups. The participants of the core stability group performed the exercise protocol three times a week for four months. These exercises consisted of five levels, and based on the gradual progress principle, their intensity was gradually increased over the four months during the study. The participants of the control group did not perform any exercise during the study. The BMD of the dominant femur neck was measured by a Dexa device, and the flexor and external rotator strength of the hip was measured by a manual dynamometer. Data analysis was performed applying paired and independent-sample t-test in SPSS23 software. The significant level was set at 0.05. Results: The results of paired samples t-test showed that the BMD of the femur neck significantly increased in the core stability group (Pvalue=0.001) and significantly decreased in the control group (Pvalue=0.045) at the post-test compared to the pre-test. Also in intra-group comparison, the flexor and external rotator strength of the hip significantly were increased in the core stability group (Pvalue=0.001 and 0.001, respectively). While there was not such a significant change in the control group. On the other hand, based on the results of the independent samples t-test, the femur neck BMD (Pvalue=0.007) and the flexor and external rotator strength of the hip (Pvalue=0.001 and 0.001, respectively) significantly increased in the core stability compared to the control group. Conclusions: According to the results, it seems that core stability exercises can be suggested to postmenopausal women as an effective strategy for osteogenic bone behavior and reducing the risk of osteoporosis. Keywords: Core stability training, Femur bone mineral density, Lower extremity muscles strength, Postmenopausal women